Spatio-temporal dynamics of floating marine macro-litter in Italian waters (2018–2023): The impact of the COVID-19 pandemic - V. Donnarumma; G. Suaria; A. Paluselli; S. Aliani; E. Pasanisi; F. Maffucci; M. Azzolin; I. Campana; A. Castelli; M. Costantino; R. Crosti; M. Farina; et al. (Environmental Pollution, 2026)

From juveniles to adults: Ontogenetic and seasonal patterns of loggerhead turtles in oceanic Mediterranean habitats - E. Pasanisi; F. Maffucci; F. Atzori; M. Azzolin; I. Campana; L. Carosso; A. Castelli; M. Costantino; L. David; N. Di-Méglio; M. Farina; O. Garcia-Garin; et al. (Marine Environmental Research, 2026)

Comparative species distribution model framework for marine conservation and its application to loggerhead turtles in the Mediterranean - E. Pasanisi; F. Maffucci; F. Atzori; M. Azzolin; I. Campana; L. Carosso; A. Castelli; M. Costantino; R. Crosti; L. David; N. Di‐Meglio; M. Farina; et al. (Conservation Biology, 2026)
Modeling species distributions in dynamic pelagic environments remains challenging, particularly for wide‐ranging and highly mobile species when there is limited guidance on model performance. This limitation constrains the effective use of species distribution models (SDMs) in marine conservation, where robust and transferable predictions are essential for conservation planning. Using the loggerhead turtle ( Caretta caretta ) as a case study, we developed a benchmarking workflow to compare modeling strategies across spatial resolutions, environmental predictor variables, and algorithms. We evaluated five common modeling approaches—generalized linear models, generalized additive models, random forest, boosted regression trees, and MaxEnt—and used a 15‐year dataset of visual surveys collected along standardized ferry‐based transects across the Mediterranean Sea, with environmental predictor variables averaged across years to capture recurrent summer conditions. Model outputs were assessed for their ability to predict habitat suitability and space‐use patterns in dynamic pelagic environments. At the same time, robustness and spatial transferability were evaluated using an independent, basin‐scale aerial survey dataset. Our results revealed consistent patterns informing SDM selection for wide‐ranging pelagic species. In offshore Mediterranean pelagic systems, increased spatial resolution improved the ecological interpretability of predicted habitat patterns, whereas an extended set of dynamic oceanographic predictors enhanced the characterization of habitat associations. Independent validation was critical for selecting robust and transferable modeling algorithms, with MaxEnt and generalized additive models providing the most reliable performance for suitability and encounter rate (ER) modeling, respectively. Combining presence‐only and encounter rate models helped distinguish habitat suitability from observation intensity. Overall, this study developed an empirically tested workflow to support robust, consistent, and policy‐relevant SDM applications for mobile marine species in offshore, data‐limited systems. By clarifying trade‐offs among modeling approaches, this framework enhanced the application of SDMs to inform spatial planning, conservation prioritization, and species distribution and habitat‐use assessments within regional and international conservation frameworks.

Portable X-ray tomography prototype for cultural heritage: design and applications - A. Mazzinghi; F. Cantini; M. Massi; L. Castelli; M. Bettuzzi; M. P. Morigi; M. Galeotti; A. Cagnini; S. Porcinai; M. Manetti; F. Taccetti; L. Giuntini (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)
X-ray radiography and tomography are widely employed techniques in the Cultural Heritage (CH) field, as testified by the large number of analyses performed for these applications in this field. Specifically, tomography provides fully non-invasive morphological and microstructural information on the internal structure of the sample and can reveal, when possible, hidden details such as ancient repairs or concealed conservation interventions. All these aspects make this technique essential both for gaining insights into production techniques and for assessing the conservation state. One of the main requirements for instrumentation employed in Heritage Science is the versatility of the equipment, as artefacts can vary considerably in size, may have complex and irregular shapes, and exhibit diverse compositions, materials, and manufacturing methods. It is therefore evident that the instrumentation must be readily adaptable to each specific application. This requirement also implies the necessity for portable and open-source equipment. The latter characteristic is of particular importance, as open-source instruments allow for extensive customisation in response to the diverse requirements of different operators. In the framework of the National recovery and Resilience Plan (PNRR) CHANGES (Cultural Heritage Innovation for Next-Gen Sustainable Society) project, a fruitful collaboration was established with the Department of Physics and Astronomy of the University of Bologna, as regards mainly the detection system, and the Opificio delle Pietre Dure (OPD), acting in the quality of end-user. Taking all the above-mentioned aspects into consideration, at the Department of Physics and Astronomy of the University of Florence and with the crucial support of the CHANGES project, we developed a portable and open-source X-ray tomography system specifically designed for Cultural Heritage applications. In this paper, we present this prototype which offers a highly customisable design that can be tailored to a wide range of operational needs. Graphic abstract

P32-01 Metabolomic analysis of human keratinocyte response to chemical sensitizers - C. Zimmer; K. Hardonnière; F. Castelli; E. Chu-Van; C. Chollet; M. Pallardy; F. Fenaille; S. Kerdine-Römer (Toxicology Letters, 2025)

Test–retest reliability of TMS motor evoked responses and silent periods during explosive voluntary isometric contractions - F. Castelli; O. S. Mian; A. Bruton; A. C. Valappil; N. A. Tillin (European Journal of Applied Physiology, 2025)
Purpose This study assessed the test–retest reliability of TMS motor evoked potentials (MEPs) and silent periods at early, middle, and late phases of the rising time–torque curve during explosive voluntary contractions. We also investigated how the number of consecutively averaged measurements influenced reliability. Methods On two separate occasions 3–7 days apart, 14 adults performed several isometric explosive (1-s) contractions of the knee extensors, some of which were superimposed with TMS to elicit MEPs in the superficial quadriceps. Of those with TMS, stimulation was timed to elicit MEPs at either 45 (early), 115 (middle), or 190 ms (late) following contraction onset (16 with-TMS contractions per time condition). TMS was also superimposed at the plateau of 15 separate MVCs. Test–retest intraclass correlation coefficient (ICC) and coefficient of variation (CV) were calculated for MEPs and silent periods consecutively averaged over 3 to 15 separate contractions. Results No one condition/phase was more reliable than another. For MEP amplitude, in all conditions except the explosive late phase, ICCs generally increased, and CV decreased, with an increase in the number of averaged contractions, and were > 0.50 ICC and < 15% CV within seven contractions. For silent period, ICCs and CVs were unaffected by the number of consecutively averaged contractions and remained > 0.50 ICC and < 10% CV. Conclusion Test–retest reliability of TMS responses is comparable between phases of explosive contraction and at the plateau of MVC. To maximise reliability of MEPs during explosive contractions or MVCs, we recommend future studies average data across more than the 3–5 contractions typically reported in the literature investigating MEPs at MVC plateau.

Calibration of the UBC3D-PLM soil model from Dilatometer Marchetti Test (DMT) for the liquefaction behaviour and cyclic resistance ratio (CRR) of sandy soils - F. Castelli; S. Grasso; V. Lentini; M.S.V. Sammito (Soil Dynamics and Earthquake Engineering, 2024)

The selection of paired watersheds affects the assessment of wildfire hydrological impacts - M. Nigro; D. Penna; I. Baneschi; G. Castelli; A. Dani; M. Menichini; L. Piemontese; P. Trucchi; F. Preti; M. Doveri; R. Giannecchini (Science of The Total Environment, 2024)

Multi-risk assessment in a historical city - C. Arrighi; M. Tanganelli; M. T. Cristofaro; V. Cardinali; A. Marra; F. Castelli; M. De Stefano (Natural Hazards, 2023)
Natural hazards pose a significant threat to historical cities which have an authentic and universal value for mankind. This study aims at codifying a multi-risk workflow for seismic and flood hazards, for site-scale applications in historical cities, which provides the Average Annual Loss for buildings within a coherent multi-exposure and multi-vulnerability framework. The proposed methodology includes a multi-risk correlation and joint probability analysis to identify the role of urban development in re-shaping risk components in historical contexts. The workflow is unified by exposure modelling which adopts the same assumptions and parameters. Seismic vulnerability is modelled through an empirical approach by assigning to each building a vulnerability value depending on the European Macroseismic Scale (EMS-98) and modifiers available in literature. Flood vulnerability is modelled by means of stage-damage curves developed for the study area and validated against ex-post damage claims. The method is applied to the city centre of Florence (Italy) listed as UNESCO World Heritage site since 1982. Direct multi-hazard, multi-vulnerability losses are modelled for four probabilistic scenarios. A multi-risk of 3.15 M€/year is estimated for the current situation. In case of adoption of local mitigation measures like floodproofing of basements and installation of steel tie rods, multi-risk reduces to 1.55 M€/yr. The analysis of multi-risk correlation and joint probability distribution shows that the historical evolution of the city centre, from the roman castrum followed by rebuilding in the Middle Ages, the late XIX century and the post WWII, has significantly affected multi-risk in the area. Three identified portions of the study area with a different multi-risk spatial probability distribution highlight that the urban development of the historical city influenced the flood hazard and the seismic vulnerability. The presented multi-risk workflow could be applied to other historical cities and further extended to other natural hazards.

MACHINA, the Movable Accelerator for Cultural Heritage In-situ Non-destructive Analysis: project overview - F. Taccetti; L. Castelli; M. Chiari; C. Czelusniak; S. Falciano; M. Fedi; F. Giambi; P. A. Mandò; M. Manetti; M. Massi; A. Mazzinghi; C. Ruberto; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)
Over the years, transportable instrumentation for cultural heritage (CH) in situ measurements has noticeably widespread, due to logistic, economical and safety reasons. Ion beam analysis, a powerful set of analytical techniques, of great importance for CH, is instead carried out by using fixed instrumentation. To overcome this limit, the Italian national Institute of Nuclear Physics (INFN), CERN (European Centre for Nuclear Research) and the Opificio delle Pietre Dure (OPD), started MACHINA, the “Movable Accelerator for CH In-situ Non-destructive Analysis: the new generation of accelerators for art” to build a transportable accelerator, compact, with strongly reduced weight, absorbed power and cost. MACHINA will be installed at the OPD and dedicated to CH. It will be moved to major conservation centres and museums, when needed. The INFN-CERN proposal, approved in December 2017, became operative in February 2018. 2018 was dedicated to the acquisition of material/instrumentations, to set up both a dummy accelerator (to test the vacuum system) and a vacuum chamber (to test the source). Due to COVID, in 2020 and 2021 the experimental work was slowed down, but we kept developing the control electronics/software and built the second-generation supporting structure. The HF-RFQ power supplies were integrated in October 2021. At the rise of 2022, after conditioning the cavities, we tested the system and in March 2022 we got the first extracted 2-MeV proton beam. In this paper, we present the structure of the MACHINA system, the approach followed and the main solutions adopted, with a special focus on the control system, and finally the first experimental results.

Novel implementation of the INFN-CHNet X-ray fluorescence scanner for the study of ancient photographs, archaeological pottery, and rock art - F. Taccetti; L. Castelli; C. Czelusniak; F. Giambi; M. Manetti; M. Massi; A. Mazzinghi; C. Ruberto; F. Arneodo; R. Torres; F. Castellá; L. Gheco; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

KIR2DL4 genetic diversity in a Brazilian population sample: implications for transcription regulation and protein diversity in samples with different ancestry backgrounds - Emiliana Weiss; Heloisa S. Andrade; Juliana Rodrigues Lara; Andreia S. Souza; Michelle A. Paz; Thálitta H. A. Lima; Iane O. P. Porto; Nayane S. B. Silva; Camila F. Bannwart Castro; Rejane M. T. Grotto; Eduardo A. Donadi; Celso T. Mendes-Junior; et al. (Immunogenetics, 2021)

The Share of the Mean Turbulent Kinetic Energy in the Near-Neutral Surface Layer for High and Low Wind Speeds - M. Schiavon; F. Tampieri; F. C. Bosveld; M. Mazzola; S. Trini Castelli; A. P. Viola; C. Yagüe (Boundary-Layer Meteorology, 2019)

A multipurpose X-ray fluorescence scanner developed for in situ analysis - F. Taccetti; L. Castelli; C. Czelusniak; N. Gelli; A. Mazzinghi; L. Palla; C. Ruberto; C. Censori; A. Lo Giudice; A. Re; D. Zafiropulos; F. Arneodo; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2019)

Investigating hydrogeomorphic floodplain mapping performance with varying DTM resolution and stream order - A. Annis; F. Nardi; R. R. Morrison; F. Castelli (Hydrological Sciences Journal, 2019)

Association between aerobic fitness and cerebrovascular function with neurocognitive functions in healthy, young adults - Jungyun Hwang; Kiyoung Kim; R. Matthew Brothers; Darla M. Castelli; F. Gonzalez-Lima (Experimental Brain Research, 2018)

Engineering Geological and Petrographic Characterization of Migmatites Belonging to the Calabria-Peloritani Orogen (Southern Italy) - G. Pappalardo; R. Punturo; S. Mineo; G. Ortolano; F. Castelli (Rock Mechanics and Rock Engineering, 2016)

Infective endocarditis in patients with hepatic diseases - E. Seminari; A. De Silvestri; V. Ravasio; S. Ludovisi; R. Utili; N. Petrosillo; F. Castelli; M. Bassetti; F. Barbaro; P. Grossi; N. Barzaghi; M. Rizzi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Oxidovanadium(IV) complexes with chrysin and silibinin: anticancer activity and mechanisms of action in a human colon adenocarcinoma model - I. E. León; J. F. Cadavid-Vargas; I. Tiscornia; V. Porro; S. Castelli; P. Katkar; A. Desideri; M. Bollati-Fogolin; S. B. Etcheverry (JBIC Journal of Biological Inorganic Chemistry, 2015)

Fragments of the Western Alpine Chain as Historic Ornamental Stones in Turin (Italy): Enhancement of Urban Geological Heritage through Geotourism - A. Borghi; A. d’Atri; L. Martire; D. Castelli; E. Costa; G. Dino; S. E. Favero Longo; S. Ferrando; L. M. Gallo; M. Giardino; C. Groppo; R. Piervittori; et al. (Geoheritage, 2014)

Mitochondrial DNA variability of the pipefish Syngnathus abaster - D. Sanna; F. Biagi; H. B. Alaya; F. Maltagliati; A. Addis; A. Romero; J. De Juan; J.‐P. Quignard; A. Castelli; P. Franzoi; P. Torricelli; M. Casu; et al. (Journal of Fish Biology, 2013)
This study provides data on the genetic structuring of the pipefish Syngnathus abaster in the western Mediterranean and Adriatic Seas. A total of 109 specimens were collected in brackish‐water biotopes. The control region and three other regions of the mitochondrial genome were analysed. The most relevant result was the high genetic structuring found by Bayesian inference ( BI ), maximum likelihood ( ML ) and network analyses, which were consistent in showing three well‐separated clusters of S. abaster populations. Furthermore, BI and ML did not support the monophyly of the taxon S. abaster . These results suggest the occurrence of a species complex in the study area, whose differentiation may have occurred since the Pleistocene. The results also show a very high genetic variability at the inter‐population level, with no shared haplotypes among sites. Evolutionary forces due to the fragmented nature of the brackish‐water habitats may account for the high genetic divergence found among the groups and populations. Finally, although dispersal by rafting over long distances may occasionally occur, this study suggests linear stepping‐stone model of colonization to be most likely. The complexity of the results obtained suggests that further studies are needed to elucidate the phylogeny of S. abaster .

Hospital-related outbreaks due to rare fungal pathogens: a review of the literature from 1990 to June 2011 - E. C. Repetto; C. G. Giacomazzi; F. Castelli (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Do mosquito-associated bacteria of the genus Asaia circulate in humans? - S. Epis; P. Gaibani; U. Ulissi; B. Chouaia; I. Ricci; C. Damiani; V. Sambri; F. Castelli; F. Buelli; D. Daffonchio; C. Bandi; G. Favia (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Helical axis calculation based on Burmester theory: experimental comparison with traditional techniques for human tibiotalar joint motion - N. Sancisi; V. Parenti-Castelli; F. Corazza; A. Leardini (Medical & Biological Engineering & Computing, 2009)

A dynamic cloud masking and filtering algorithm for MSG retrieval of land surface temperature - F. Baroncini; F. Castelli; F. Caparrini; S. Ruffo (International Journal of Remote Sensing, 2008)

The 1780 seismic sequence in NE Sicily (Italy): shifting an underestimated and mislocated earthquake to a seismically low rate zone - R. Azzaro; F. Bernardini; R. Camassi; V. Castelli (Natural Hazards, 2007)

Mathematical model for pre-operative planning of linear and closing-wedge metatarsal osteotomies for the correction of hallux valgus - F. Bettazzoni; A. Leardini; V. Parenti-Castelli; S. Giannini (Medical & Biological Engineering & Computing, 2004)

Cu 2+ , Co 2+ , and Mn 2+ Modify the Gating Kinetics of High-Voltage-Activated Ca 2+ Channels in Rat Palaeocortical Neurons - L. Castelli; F. Tanzi; V. Taglietti; J. Magistretti (The Journal of Membrane Biology, 2003)

Is Syllis gracilis (Polychaeta: Syllidae) a species complex? An allozyme perspective - F. Maltagliati; A. P. Peru; M. Casu; F. Rossi; C. Lardicci; M. Curini-Galletti; A. Castelli (Marine Biology, 2000)

Higher Short-Term Virologic Efficacy of Three-Class Versus Two-Class Highly Active Antiretroviral Salvage Therapy in HIV-Infected Patients - F. Baldanti; S. Paolucci; R. Maserati; F. Maggiolo; A. Pan; F. Castelli; R. Gulminetti; G. Comolli; A. Chiesa; G. Gerna (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Comparison of pharmacokinetics and dynamics of two dosage regimens of foscarnet in AIDS patients with Cytomegalovirus retinitis - F. Castelli; L. Tomasoni; C. Zeroli; F. Suter; G. Trespi; G. Carosi; A. Hedman (European Journal of Clinical Pharmacology, 1997)

Restriction endonuclease mapping and molecular cloning of the human herpesvirus 6 variant B strain Z29 genome - G. J. Lindquester; N. Inoue; R. D. Allen; J. W. Castelli; F. R. Stamey; T. R. Dambaugh; J. J. O'Brian; R. M. Danovich; N. Frenkel; P. E. Pellett (Archives of Virology, 1996)

Expression and analysis of the NS2 protein of influenza A virus - A. C. Ward; L. A. Castelli; A. C. Lucantoni; J. F. White; A. A. Azad; I. G. Macreadie (Archives of Virology, 1995)

2,3,7,8-Tetrachlorodibenzo-p-dioxin toxic effects and tissue levels in animals from the contaminated area of seveso, Italy - R. Fanelli; M. P. Bertoni; M. G. Castelli; C. Chiabrando; G. P. Martelli; A. Noseda; S. Garattini; C. Binaghi; V. Marazza; F. Pezza (Archives of Environmental Contamination and Toxicology, 1980)